2021
DOI: 10.1177/0003489421996968
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Robotic Surgery Training Among Otolaryngology—Head and Neck Surgery Residents

Abstract: Objective: The aim of this study is to describe the current state of robotic surgery training among Otolaryngology—Head and Neck Surgery (OHNS) residency programs in the United States. Methods: This is a national survey study among OHNS residents. All OHNS residency programs were identified via the Accreditation Council for Graduate Medical Education website. A total of 64/127 (50.3%) of OHNS programs were selected based on a random number generator. The main outcome measure was the number of OHNS residents wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Preliminary studies have shown that intraoperative imaging using ICG is both a feasible and safe approach for head and neck tumors. It has been shown to be effective in identifying parathyroid glands and their respective vascularization 33,34 and our research group has significant experience in TORS 35–38 . However, there is a current gap in knowledge regarding the role of the underlying vascular pathophysiology and its effect on the resulting ICG signal during FI‐guided surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary studies have shown that intraoperative imaging using ICG is both a feasible and safe approach for head and neck tumors. It has been shown to be effective in identifying parathyroid glands and their respective vascularization 33,34 and our research group has significant experience in TORS 35–38 . However, there is a current gap in knowledge regarding the role of the underlying vascular pathophysiology and its effect on the resulting ICG signal during FI‐guided surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to be effective in identifying parathyroid glands and their respective vascularization 33,34 and our research group has significant experience in TORS. [35][36][37][38] However, there is a current gap in knowledge regarding the role of the underlying vascular pathophysiology and its effect on the resulting ICG signal during FI-guided surgery. Head and neck tumors are hypervascular 39,40 ; however, the importance of vascular permeability to improve surgical visualization has not been explored.…”
mentioning
confidence: 99%